THE INFLUENCE OF GREEN PRODUCT AND WORD OF MOUTH (WOM) ON PURCHASE DECISIONS THROUGH PURCHASE INTENTION AS AN INTERVENING VARIABLE AMONG FORE COFFEE KEDIRI CONSUMERS - Sella Selviana; Erwin Syahputra (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Fore Coffee Kediri faces challenges in maximizing environment-based marketing strategies and social recommendations, despite favorite menu items like Es Aren Latte and Es Pandan Latte selling out within 6 hours per day. However, low attention to green input, process, and output aspects, as well as suboptimal utilization of word of mouth (WOM), causes purchase intention and purchase decisions to remain suboptimal. This study aims to examine the influence of green product and WOM on purchase decisions, with purchase intention as an intervening variable. The method used is a quantitative survey with 160 active consumer respondents of Fore Coffee Kediri, analyzed using SEM-PLS. The research results show that green product does not have a significant direct influence on purchase decisions, but significantly influences purchase intention. Similarly, WOM does not directly influence purchase decisions, but is significant toward purchase intention. Purchase intention is proven to significantly influence purchase decisions, and significantly mediates the influence of green product and WOM on purchase decisions. This model explains 83.3% of purchase decision variability and 22.3% of purchase intention variables. These findings confirm the importance of strategies that strengthen purchase intention to maximize purchase decisions among Fore Coffee Kediri consumers.